NICU Fathers: Improving the Quality of Paternal Support in the NICU. (October 2021) - LeDuff, Lawrence D.; Carter, Brigit M.; Cunningham, Craig A.; Braun, Lisa A.; Gallaher, Keith J.
Abstract : Background: Parental support in the neonatal intensive care unit (NICU) is critical; yet, the nursing staff may struggle to provide optimal support to NICU fathers. Generally, fathers are not viewed as equally competent caregivers when compared with mothers, and fathers often impart these beliefs on themselves. Increasing the nursing staff's knowledge and understanding of paternal support can change attitudes and foster positive behavior changes, enhancing the perception of support received by NICU fathers. Purpose: To implement a needs assessment and educational intervention for the nursing staff designed to increase the perception of nursing support received by NICU fathers. Methods: The Nurse Parents Support Tool (NPST) was administered to the clinical nursing staff and fathers in a pre/posttest design comparing support given by nurses with the fathers' perception of received support. Data from the preintervention assessment was used to design an educational intervention on improving fathers' support. Following the intervention, a postintervention NPST was administered to fathers to determine whether there was an improvement in support perception. Findings/Results: Improvement in the NICU fathers' perception of nursing staff support was noted between father groups. In addition, the NPST can be used to assess paternal support needs and develop staff education. Implications for Practice: Support provided to NICU fathers can enhance the father's perception of himself as an equal and competent caregiver, leading to improved father–infant bonding as the child ages. Educational interventions targeting father support should be a routine part of nursing staff training. Implications for Research: Future research should examine the long-term effects of early paternal support on psychosocial, cognitive, and developmental outcomes of NICU infants.